Dendritic cell-based vaccines: clinical applications in breast cancer. (March 2014) - Gelao, Lucia; Criscitiello, Carmen; Esposito, Angela; Laurentiis, Michele De; Fumagalli, Luca; Locatelli, Marzia Adelia; Minchella, Ida; Santangelo, Michele; Placido, Sabino De; Goldhirsch, Aron; Curigliano, Giuseppe
Abstract: : Recent evidence suggests that the immune system is involved in the carcinogenesis process and the antitumor immune responses impact the clinical outcome, thus emphasizing the concept of cancer immune surveillance. In this context, dendritic cells (DCs) seem to play a crucial role, as they are the most potent antigen-presenting cells (APCs) and are able to stimulate naive T lymphocytes and to generate memory T lymphocytes. Immunotherapy with DC-based vaccines is a very attractive approach to treat cancer, offering the potential for high tumor-specific cytotoxicity. Although breast cancer (BC) is traditionally considered a poorly immunogenic tumor, increasing numbers of both preclinical and clinical studies demonstrate that vaccination with DCs is capable of inducing an antitumor-specific response, while being well tolerated and safe. However, clinical objective responses are still disappointing and many reasons may explain the difficulty of developing effective DC-based therapies for BC. In this review, we discuss the characteristics of DCs, and the major clinical indications for DC-based immunotherapy in BC with related drawbacks.